Impacts of Urbanization on the Use of Soil Amendments by Rice Farmers Along a Rural-Urban Continuum in Northeast Thailand - Yodda, Sujitra; Laohasiriwong, Suwit; Lawongsa, Phrueksa; Sukitprapanon, Tanabhat-Sakorn; Rambo, A. Terry (Forest and Society, 2025)
This study investigated the impact of urbanization on use of soil amendment by rice farmers in three villages along a rural–urban continuum in Northeast Thailand. It shows how urbanization influences their use of types and quantities of soil amendments. Data were collected by interviewing 150 farmers, focusing on types, quantities, sources, costs, and perceived effects of nine different amendments, including rice straw, chemical fertilizers, manures, and green manure. Results revealed significant declines in organic amendment use as villages become more urbanized, with rural farmers employing more diverse and greater quantities of organic amendments while periurban and urban farmers predominantly rely on chemical fertilizers. Quantitative analysis shows that livestock manure use diminishes sharply from over 80% of farmers in rural villages to around 30% in more urbanized communities, reflecting reduced livestock numbers. Discriminant analysis compared the three villages in terms of three dependent variables. (area of paddy fields, quantities of chemical fertilizer and organic amendments applied) showed clearly that all the group means were significantly different. Analysis of quantities of chemical fertilizer and organic amendments applied by individual farmers in all three villages revealed that farmers applying higher amounts of organic matter tended to use less chemical fertilizer. Constraints, including limited supplies, high costs, and labor shortages, inhibited organic amendment application among urbanized farmers. These shifts pose a serious threat to long-term soil quality. The findings underscore the urgent need for policy interventions to promote sustainable organic soil management practices in urbanizing communities to improve soil health and food security.